Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan dan Komisaris Independen terhadap Tax Avoidance (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Logam yang terdaftar di BEI periode tahun 2018-2022) - Murni, Yetty; Tobing, Grace Yohana; Utami, Khalida (Universitas Kristen Krida Wacana, 2023)
Tax Avoidance is a company's effort to minimize the corporate tax burden paid by looking for weaknesses in tax regulations. This study aims to examine the effect of profitability, leverage, company size and independent commissioners on tax avoidance in metal sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The sample of this study consisted of 10 metal sub-sector manufacturing companies listed on the IDX which were selected by purposive sampling method. The analysis technique used in this research is analysis using multiple linear regression with the Eviews-12 program. The results of this study indicate profitability, and independent commissioners have a negative effect on tax avoidance, while the leverage variable and company size have no effect on tax avoidance. And the results of the determinant value (R2) in this study amounted to 28.7%, meaning that profitability, leverage, company size and independent commissioners contributed 28.7% to tax avoidance and the remaining 71.3% was explained by other variables not used in this study. Keywords : Profitability, Leverage, Company Size, Independent Commissioner on Tax Avoidance.